PENGARUH KUALITAS SUMBER DAYA MANUSIA, BUDAYA KERJA, DAN IKLIM ORGANISASI TERHADAP KINERJA SEKRETARIAT DEWAN PERWAKILAN RAKYAT DAERAH KABUPATEN BOGOR - Dadan - Nurdiansyah (Universitas Nasional, 2017)
This study was conducted to analyze the Influence of Quality of Human Resources, Work Culture and Organizational Climate toward Legislative Council Secretariat Performance, Bogor Regency. Reference theory study variables using the theory of Human Resources of Sedarmayanti (2014: 13), the theory of Work Culture of Paramita (in Umam, 2012: 15), the theory of Organizational Climate of Denison (in Wirawan, 2008: 124), and the theoretical performance of Moeheriono (2010: 63). This study uses a quantitative explanatory. The study population numbered 133 consists of a Chairman and members of DPRD Bogor and Bogor Regency DPRD Secretariat staff, with Slovin (5%) in the can 100 samples and each respondent get as many questions as 46 statements using a Likert scale. Based on the results showed a positive and significant influences of the Quality of Human Resources toward the Performance Legislative Council Secretariat Performance, Bogor Regency. The amount of influence Quality of Human Resources toward the Performance Legislative Council Secretariat Performance to 60.4%. There is a positive and significant Influence of Work Culture toward Legislative Council Secretariat Performance, Bogor Regency. The amount of Influence of Work Culture toward Legislative Council Secretariat Performance amounted to 61.2%. There is a positive and significant Influence of Organizational Climate toward Legislative Council Secretariat Performance, Bogor Regency . The amount of Influence of Organizational Climate toward Legislative Council Secretariat Performance to 63%. There is a positive and significant Influence of Quality of Human Resources, Work Culture and Organizational Climate together toward Legislative Council Secretariat Performance, Bogor Regency. The amount of Quality of Human Resources, Work Culture and Organizational Climate together toward Legislative Council Secretariat Performance together amounted to 73.3%.